Effect of time and density of microorganisms on bioremediation of mangrove sediment with petroleum - Silva Conceicao, Lavinia; Francisco de Oliveira, Eddy Jose; de Jesus Silva, Marcio; Moraes de Jesus, Gisele; de Souza Queiroz, Antonio Fernando; Cordeiro de Oliveira, Olivia Maria; Ferreira Lima, Danusia (Open Science Journal, 2022)
The application of bioremediation in mangroves has been growing and requiring optimization. This study aimed to assess the factor that has the greatest influence on bioremediation; and to correlate the variable time with the density of intercropping for the degradation of oil through a factorial design 22. For this, an experiment was set up with 7 bioreactors containing mangrove sediment, oil and microbial intercropped with natural polymers. The intercropping density and time variables were used to assess the system's behavior during the process. The experiment was collected in three stages, for analysis of petroleum hydrocarbons (HTP) and microorganism count (UFC). The answer to this process was obtained using the HTP / UCM ratio. The results shown that either time has a significant influence on the process. The R2 for the proposed model was 0.934, explaining 93.4% of the data from the bioremediation process. .